Dissemination of IncQ1 Plasmids Harboring NTEKPC-IId in a Brazilian Hospital - Camila Maria dos Santos Boralli; Julian Andres Paganini; Rodrigo Silva Meneses; Camila Pacheco Silveira Martins da Mata; Edna Marilea Meireles Leite; Anita C. Schürch; Fernanda L. Paganelli; Rob J. L. Willems; Ilana L. B. C. Camargo (Microorganisms)
KPC is a clinically significant serine carbapenemase in most countries, and its rapid spread threatens global public health. blaKPC transmission is commonly mediated by Tn4401 transposons. The blaKPC gene has also been found in non-Tn4401 elements (NTEKPC). To fill the gap in the understanding of the stability and dissemination of NTEKPC-carrying plasmids, we selected and characterized carbapenem-resistant bacteria isolated between 2009 and 2016 from a hospital for a retrospective study of their plasmids conjugation capacity, impact on fitness, and replication in different species. Different clones were selected using PFGE, and their genomes were sequenced using Illumina and Oxford Nanopore methods. Minimum inhibitory concentrations (MICs) were determined by broth microdilution. Plasmid copy numbers (PCNs) were determined using qPCR. Doubling time was used to analyze fitness change. Most isolates (67%, 33/49) carried blaKPC, of which 85% presented blaKPC in a NTEKPC. The 25 isolates selected presented the blaKPC gene in NTEKPC-IId in IncQ1-type plasmids, showing multispecies dissemination. IncQ1 plasmids were mobilizable and PCN seemed to be directly linked to the species, presenting a high-copy number, mainly in K. pneumoniae. No relationship was observed between IncQ1 PCN and carbapenems MIC values. IncQ1 and a conjugative plasmid from K. pneumoniae BHKPC10 were transferred to E. coli J53 without fitness changes, and MIC values were maintained for carbapenems despite the low transconjugant PCN. In addition to IncQ1 with NTEKPC, Enterobacter cloacae BHKPC28 contained the mcr-9 gene in an IncHI2/IncHI2A conjugative plasmid, which may help the mobility of IncQ1 and the dissemination of two resistance determinants to last-resort antibiotics. Understanding the interaction between plasmids and high-risk lineages can help develop new therapies to prevent the dissemination of resistance traits.